ReconOS64 - Hardware-Software Multithreading for Heterogeneous Platform FPGAs - Clausing, Lennart
Heterogeneous computing devices comprising multiple processing systems combined with a programmable logic like an FPGA have become increasingly popular. Developing and runtime managing these heterogeneous platform devices, however, still poses multiple challenges. The programming paradigms for hardware and software applications fundamentally differ, while the runtime management requires additional attention. The first steps towards unifying design flows have been taken by creating high-level synthesis tools. However, these toolsfocus on the design process and lack runtime management features. FPGA operating systems aim to close this gap by providing runtime management features and build tools. ReconOS, as an example of an FPGA operating system, allows bridging the hardware-software gap by integrating hardware-located computation units as threads into a host operating system, allowing for familiar inter-thread programming paradigms to be extended to FPGAs. This thesis presents ReconOS64, a successor and fork of ReconOS, aiming at modern 64-bit platform systems-on-chip. Besides establishing support for this platform and incorporating new system generation processes, ReconOS64 provides additional features for both development and runtime management. By providing a flexible grouping mechanism for hardware-located threads, partial reconfiguration for exchanging individual threads at runtime is simplified. Further runtime flexibility was achieved by implementing a multi-clock architecture, allowing individual groups of threads to be executed at different frequencies, which can be adapted during runtime with a low reconfiguration overhead. In addition, this thesis provides an overview of further development approaches on various systems based on ReconOS64 and ReconOS.

On Guaranteeing Schedulability of Periodic Real-time Hardware Tasks under ReconOS64 - Clausing, Lennart; Guetattfi, Zakarya; Kaufmann, Paul; Lienen, Christian; Platzner, Marco (Proceedings of the 19th International Symposium on Applied Reconfigurable Computing (ARC))

Flexible Industrial Analytics on Reconfigurable Systems-On-Chip - Boschmann, Alexander; Clausing, Lennart; Jentzsch, Felix; Ghasemzadeh Mohammadi, Hassan; Platzner, Marco (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

ReconOS64: A Hardware Operating System for Modern Platform FPGAs with 64-Bit Support - Clausing, Lennart; Platzner, Marco (2022 IEEE International Parallel and Distributed Processing Symposium Workshops (IPDPSW))

ReconOS64: High-Performance Embedded Computing for Industrial Analytics on a Reconfigurable System-on-Chip - Clausing, Lennart (Proceedings of the 11th International Symposium on Highly Efficient Accelerators and Reconfigurable Technologies)

Development of a Hardware / Software Codesign for sonification of LIDAR-based sensor data - Clausing, Lennart